Ethics in the Notarial Profession - Makoter Rožmarin, Matej (65 pravne znanosti v Mariboru, 2026)
This chapter examines selected aspects of ethics in the notarial profession as a cornerstone of public trust. The historical development of the Latin-type notariat shows that a notary must not only be professionally qualified but also personally suited to uphold high ethical standards. Notaries are guided by professional ethics and by the public’s expectation that they embody integrity and social responsibility. They must therefore adhere to ethical and moral principles both in exercising their official powers and in their private conduct. The chapter explores the role of ethics in shaping notaries’ work as persons of public trust, its influence on their conduct in legal transactions, and its importance in the appointment of new notaries. It also considers relevant case law and offers a comparative perspective on the regulation of ethics in the Croatian notarial profession. Finally, it proposes solutions for strengthening the integration of ethical principles into the Slovenian legislative framework, addressing in particular confidentiality and the duty to provide explanations.